Between the processes of strengthening and weakening of the Family Health Strategy - Spagnuolo, Regina Stella [UNESP]; Bocchi, Silvia Cristina Mangini [UNESP] (Associação Brasileira de Enfermagem, 2013)
This was a qualitative study with the purpose of designing a meta-model for the work process of the Family Health Strategy (FHS) team. It was based on the experience of six sample groups, composed of their members (physicians, professional nurses, dentists, dental assistants, licensed technical nurses and community health agents) in a city in São Paulo state, Brazil, totaling 54 subjects. Six theoretical models emerged from non-directive interviews. These were analyzed according to Grounded Theory and submitted to the meta-synthesis strategy, which produced the meta-model between the processes of strengthening and weakening of the FHS model: professional-team-community reciprocity as an intervening component. When analyzed in light of the Theory of Complexity (TC), it showed to be a work with a vertical and authoritarian tendency, which is largely hegemonic in the tradition of public health care policies.

Pesquisa qualitativa, em que se elaborou um metamodelo do processo de trabalho da Estratégia Saúde da Família (ESF), a partir da experiência de seis grupos amostrais: médicos, enfermeiros, cirurgiões dentistas, auxiliares de cirurgião dentista, auxiliares de enfermagem e agentes comunitários de saúde, de um município do interior paulista, perfazendo 54 atores. Das entrevistas não diretivas, analisadas segundo a Teoria Fundamentada nos Dados, emergiram seis modelos teóricos, os quais foram submetidos à estratégia de metassíntese, produzindo o metamodelo entre os processos de fortalecimento e de fragilização do modelo ESF: reciprocidade profissional - equipe - comunidade como componente interveniente. Analisado à luz da Teoria da Complexidade (TC), revelou-se um trabalho de tendência verticalizada e autoritária, largamente hegemônico na tradição das políticas públicas de saúde.

En esta investigación cualitativa se elaboró un metamodelo del proceso de trabajo de la Estrategia Salud de la Familia (ESF) con base en la experiencia de seis grupos de muestras: médicos, enfermeros, cirujanos dentistas, auxiliares de cirujano dentista, auxiliares de enfermería y agentes comunitarios de salud de un municipio del interior de São Paulo, con un total de 54 actores. De las entrevistas no directivas, analizadas según el Muestreo Teórico, emergieron seis modelos teóricos que se sometieron a la estrategia de meta síntesis y produjeron el metamodelo entre los procesos de fortalecimiento y de debilitamiento del modelo ESF: reciprocidad profesional - equipo - comunidad como componente interviniente. Analizado a la luz de la Teoría de la Complejidad (TC) se reveló un trabajo de tendencia vertical y autoritaria, largamente hegemónico en la tradición de las políticas públicas de salud.
Entre os processos de fortalecimento e de fragilização da Estratégia Saúde da Família
Entre los procesos de fortalecimiento e de debilitamiento de la Estrategia Salud de la Familia
Keywords: Programa Saúde da Família; Saúde Pública; Dinâmica não Linear; Pesquisa Qualitativa; Family Health Program; Public Health; Non-Linear Dynamics; Qualitative Research